Anesthesia and Monitoring in Small Laboratory Mammals Used in Anesthesiology, Respiratory and Critical Care Research: A Systematic Review on the Current Reporting in Top-10 Impact Factor Ranked Journals. - Christopher Uhlig; Hannes Krause; Thea Koch; Marcelo Gama de Abreu; Peter Markus Spieth (PLoS ONE)
Rationale This study aimed to investigate the quality of reporting of anesthesia and euthanasia in experimental studies in small laboratory mammals published in the top ten impact factor journals. Methods A descriptive systematic review was conducted and data was abstracted from the ten highest ranked journals with respect to impact factor in the categories 'Anesthesiology', 'Critical Care Medicine' and 'Respiratory System' as defined by the 2012 Journal Citation Reports. Inclusion criteria according to PICOS criteria were as follows: 1) population: small laboratory mammals; 2) intervention: any form of anesthesia and/or euthanasia; 3) comparison: not specified; 4) primary outcome: type of anesthesia, anesthetic agents and type of euthanasia; secondary outcome: animal characteristics, monitoring, mechanical ventilation, fluid management, postoperative pain therapy, animal care approval, sample size calculation and performed interventions; 5) study: experimental studies. Anesthesia, euthanasia, and monitoring were analyzed per performed intervention in each article. Results The search yielded 845 articles with 1,041 interventions of interest. Throughout the manuscripts we found poor quality and frequency of reporting with respect to completeness of data on animal characteristics as well as euthanasia, while anesthesia (732/1041, 70.3%) and interventions without survival (970/1041, 93.2%) per se were frequently reported. Premedication and neuromuscular blocking agents were reported in 169/732 (23.1%) and 38/732 (5.2%) interventions, respectively. Frequency of reporting of analgesia during (117/610, 19.1%) and after painful procedures (38/364, 10.4%) was low. Euthanasia practice was reported as anesthesia (348/501, 69%), transcardial perfusion (37/501, 8%), carbon dioxide (26/501, 6%), decapitation (22/501, 5%), exsanguination (23/501, 5%), other (25/501, 5%) and not specified (20/501, 4%, respectively. Conclusions The present systematic review revealed insufficient reporting of anesthesia and euthanasia methods throughout experimental studies in small laboratory mammals. Specific guidelines for anesthesia and euthanasia regimens should be considered to achieve comparability, quality of animal experiments and animal welfare. These measures are of special interest when translating experimental findings to future clinical applications.